PENGARUH KOMPENSASI, KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL MENARA PENINSULA JAKARTA - Raudina Fahmi Husnina; Chatarina Yunita Tarigan (LPPM Universitas Asa Indonesia, 2020)
The purpose of this study is to analyze the effect of compensation, leadership, and work discipline on employee performance both partially and simultaneously at Menara Peninsula Hotel Jakarta. The population of this study were 306 respondents, the sample used in this study was 100 respondents. The sampling technique used was purposive technique due to time limitation and efficiency. Data collection technique using questionnaire that has been tested for its validity and realibility. Data were analyzed by descriptive and quatitative. The regression analysis started with the classical assumption test (normality test, multicollinearity test, heteroscedaticity test, linearity test) afterward by multiple linear regression analysis. The model determined by hypotheses testing applied F test, t test, correlation test, and the coefficient determination (R2). The result showed that the compensation has a significant effect on employee performance, the leadership has a significant effect on employee performance, and the work discipline has a significant effect on employee performance, where all variables simultaneously have a positive effect on employee performance at Menara Peninsula Hotel Jakarta.